Gambaran Perilaku Berisiko HIV pada Pengguna Napza Suntik di Provinsi Jawa Tengah - Cahyani, Amalia Eka; Widjanarko, Bagoes; Laksono, Budi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTDescription of Risk Behaviors HIV Among Injecting Drug Users In Central Java Province; Injecting drug users (IDUs) is the high risk population that was vulnerable to HIV infection. IDUs not only contribute HIV through unsafe injecting behavior but also through risky sexual behavior. The HIV prevalence among IDUs in Indonesia still highest position it was reached 41% in 2011. In Central Java province percentage factor for HIV transmission risk through unsafe injecting among IDUs is still high, it was 7.7%. The high number cases of HIV in IDU’s would be worried, it can be predicted that cases of HIV would spread to general population. This study aims to describe HIV risk behaviors among IDUs in Central Java Province. This research is a quantitative with cross sectional approach. The number of respondents in this study was 172 IDUs in Central Java Province. Analysis of data using univariate analysis with frequency distribution. The results showed the hiv risk behavior of injecting drug use that 8% of IDUs reported sharing needle without bleaching. On sexual behavior patterns majority of respondents (37.2%) had one partner and not using a condom at last sex.Keywords: IDU’s, HIV Risk Behaviors, Central Java Province